DIVERSI TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM DI TINGKAT PENYIDIKAN (STUDI DI POLRESTA MEDAN) - Yati Sharfina Desiandri; Madiasa Ablisar; Marlina Marlina; Edy Ikhsan (Universitas Sumatera Utara, 2017)
ABSTRACT Diversion is the duty of law enforcer handling the case of criminal offenses committed by children to take action to continue or discontinue court cases. Diversion in an effort to urge people to obey and uphold the laws of the country, its implementation still consider fairness as the top priority in addition to providing the opportunity for offenders to take the path of non-criminal as compensation, social work or supervision of their parents. Investigation authority possessed by police is the initial process in a juvenile justice process. This is due, whether or not children in conflict with the law are processed in juvenile justice is highly dependent on the results of investigations conducted by the Police by first asking for consideration or advice from community mentors. In the case of children in conflict with the law, the police in the execution of discretion can upgrade the case so that the child does not have to deal with a formal court settlement. The formulation of the research problem in this study is the first, the effect of the diversion of children in conflict with the law. Second, synchronization regulations on diversion of children in conflict with the law in Indonesia at the level of investigation. Third, the implementation of the diversion of children in conflict with the law in Medan Police. Diversion done to prevent children perpetrators of the negative impact of the implementation of the juvenile justice practice. Diversion is an idea if the appropriate consideration to avoid the stigma in children. Diversion has a positive and negative influence for children and the other parties involved. There are differences between the Secret Telegram with legislation that is in the application of the diversion of children in terms of the threat of punishment, child investigators, diversion agreement and coordination with the prosecution (the prosecutor) and the determination made by the local District Court. On the implementation of diversion in Medan Police, guidelines used namely Act No. 11 of 2012, the Criminal Police Secret Telegram TR / 1124 / XI / 2006 and TR / 395 / DIT, VI / 2008 but has not made the PP 65 Year 2015 as the Guidelines for the implementation of diversion. There are some reasons why the diversion implementation by the police does not comply with the rules in the Act No. 11 Year 2012. There should be rules governing the supervision of the implementation of diversion. Police should own internal regulations relating to the implementation of diversion and adapted to the legislation in force. Keywords: Diversion, Children in conflict with the law, Investigation